Fishery profiling and stock assessment of blue swimming crabs, Portunus pelagicus in Maqueda Bay. - Dacuro, Donabel B.; Tan, Irene L. (Donabel B. Dacuro, 2018)
Fishing of blue swimming crabs in Maqueda Bay greatly contributes to the fisheries of Region 8. The present study assessed the fishing and marketing practices of Maqueda Bay from two sampling sites located in Brgy. 4, San Sebastian, Samar and Brgy. Pangdan, Catbalogan City. From the 246 respondents, crab fishers were all male and married, thirty-two percent fell under the age bracket of 41-50 years old. Furthermore, 37% of crab fishers were elementary graduate. In terms of the distribution of BSC, 41% of blue crab products are directly distributed to buying stations and 40% to cooking stations. Crab gillnet was the commonly used gear which is used by 67% of crabbers. The catch and catch rates based on daily catch and catch per unit effort from July to November 2014 were also estimated. High fishing pressure along with increasing fishing effort caused the daily catch rates and catch per unit effort of crabbers to decrease with the lowest recorded CPUE of 0.09 kg/segment-hr. The overall ratio of males to females was 1.6:1.0. Carapace widths ranging from 4.5 to 17 cm were caught using both gears. The mean catch caught by both gear fell under the length of sexual maturity as estimated by Ingles (1996), 9.64 cm for males and 10.6 cm for females, respectively. The stock assessment was done using the monthly length frequency data. The total value computed from fishing mortality (5.12) was relatively higher than the natural mortality (2.93). The value obtained for the exploitation rate (0.64) was higher than the optimal value of 0.38 which indicates a high level of exploitation. An effective management measure is therefore recommended to protect the stock of BSC from further exploitation in Maqueda Bay.